2022
DOI: 10.1063/5.0053693
|View full text |Cite
|
Sign up to set email alerts
|

The role of pre-existing heterogeneities in materials under shock and spall

Abstract: There has been a challenge for many decades to understand how heterogeneities influence the behavior of materials under shock loading, eventually leading to spall formation and failure. Experimental, analytical, and computational techniques have matured to the point where systematic studies of materials with complex microstructures under shock loading and the associated failure mechanisms are feasible. This is enabled by more accurate diagnostics as well as characterization methods. As interest in complex mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…From this emission it is concluded that the presence of a void or other defect-generation site can significantly lower the threshold for dislocation activity and the beginning of plasticity within diamond, depending on its orientation. This effect has been previously analyzed and quantified by Traiviratana et al, 22 Bringa et al, 23 and Flanagan et al 18,19 for other materials and is a direct consequence of the increased maximum shear stress generated by the presence of a void. The threshold stress is also dependent on void size, as has been demonstrated.…”
Section: Articlementioning
confidence: 87%
See 2 more Smart Citations
“…From this emission it is concluded that the presence of a void or other defect-generation site can significantly lower the threshold for dislocation activity and the beginning of plasticity within diamond, depending on its orientation. This effect has been previously analyzed and quantified by Traiviratana et al, 22 Bringa et al, 23 and Flanagan et al 18,19 for other materials and is a direct consequence of the increased maximum shear stress generated by the presence of a void. The threshold stress is also dependent on void size, as has been demonstrated.…”
Section: Articlementioning
confidence: 87%
“…The normal stress at the void surface is zero (traction free), generating maximal shear stresses at 45 to it. This was quantified by Traiviratana et al, 22 Bringa et al, 23 and Flanagan et al, 18,19 among others. [24][25][26][27][28][29] Thus, a 4-nm (diameter) void was introduced in our simulations in order to increase the local stresses within our simulation and stimulate the generation of defects in diamond.…”
Section: Shear Stresses Generated In Shock Compressionmentioning
confidence: 97%
See 1 more Smart Citation
“…Predicting nucleation and growth of void damage in ductile metals under dynamic loading remains a challenging problem to which much effort has been devoted (1)(2)(3)(4)(5)(6). Under shock and subsequent release loading, it is well known that the interaction of the resulting rarefaction waves can lead to the creation of a region of transient tensile stress, eventually inducing nucleation of voids at defects in the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Department of Mechanical and Aerospace Engineering, University of California San Diego, 9500 Gilman Drive, La Jolla, CA 92093, USA 2. Los Alamos National Laboratory, Los Alamos, NM 87545, USA 3. Program in Materials Science and Engineering, University of California San Diego, La Jolla, CA 92093, USA.…”
mentioning
confidence: 99%